Penyuluhan dan Implementasi Penggunaan Custom Foot Orthosis Dalam Mengurangi Derajat Flat foot - Atika Febri Anggriani; Prasetyo Catur Utomo (Jurnal Pengabdian Teknologi Informasi dan Kesehatan (DIANKES), 2023)
Flat foot is the longitudinal curvature of the medial foot. In prosthetic orthotics, flat foot is treatment using custom foot orthosis. Flat foot can be easily detected in children aged 8-12 years. From the results of early detection at SD Negeri 1 Gedongan, Colomadu, Karanganyar, 12 students had flat foot. So it is necessary to have education for the teachers and students to increase understanding of the use of custom foot orthosis in reducing the degree of flat foot in students. This activity was at SD Negeri 1 Gedongan, Colomadu, Karanganyar there are early detection of flat foot, educations, and intervention in the provision of custom foot orthosis for students who had flat foot from June to August 2022. Results: There was an increase in understanding of the use foot orthoses to reduce flat foot as evidenced by interactive discussions and evaluations with questions and answers to participants and an increased grade of flat foot students after 1 month of being given foot orthoses. Custom foot orthosis is given to students who detect flat foot to be used every day so that it provides benefits in reducing the degree of flat foot. It can help students be more comfortable in carrying out their daily activities because the curved arch can correct the condition of the arch. Implementation of the use of custom foot orthosis in reducing the degree of flat foot can help the community in dealing with flat foot in children.